Phosphorus improves pasture growth - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Researchers at the International Centre for Agricultural Research in the Dry Areas (ICARDA) have succeeded in developing a system of pasture and livestock management that will increase livestock production while rehabilitating land not suitable for...